Neuro-Logic: The Principles of Lesion Localization in Patients with Neurological Symptoms - Douglas Gelb (Association of American Medical Colleges, 2006)
Abstract Neuro-Logic is an interactive tutorial designed to teach a systematic approach to localization. The module consists of 51 cases, each with a different combination of neurologic symptoms. For each case, learners are asked to identify all the levels of the central nervous system where a single unilateral lesion could produce all of the listed symptoms. Learners who give the correct response are allowed to proceed to the next case; those with an incorrect response are drilled on the routes of the specific pathways within the nervous system corresponding to each symptom listed in the case. They are then taught to localize the lesion by identifying all sites where the pathways are near each other. The individual symptoms are repeated in various combinations scattered throughout the tutorial, so students learn the pathways corresponding to each symptom. The general reasoning approach-identify the pathways and then find the sites where all the pathways are near each other-is reinforced with each new case. By the end of a 4-week clinical neurology clerkship, learners who use this tutorial during the clerkship doubled their baseline scores on a quiz of neurologic localization.